Analysis of Digital Marketing Strategy at Mandiri Tunas Finance in Building and Maintaining Consumer Trust in Bandar Lampung - Sheva Antalia; Dora Rinova (International Journal of Business and Quality Research, 2026)
This study aims to analyze the role of digital marketing strategies in building and maintaining consumer trust at Mandiri Tunas Finance (MTF) Bandar Lampung. In the era of rapid digital transformation, financial service companies are required to adopt effective digital marketing approaches to remain competitive and credible. Consumer trust becomes a crucial factor in the financing industry due to the high level of perceived risk in financial transactions. This research employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving consumers and internal marketing staff of MTF Bandar Lampung. The findings reveal that MTF utilizes social media platforms, an official website, and digital communication channels to enhance information transparency, strengthen corporate image, and foster long-term relationships with customers. Consumer trust is built through consistent marketing messages, responsive digital services, clear product information, and the strong reputation of its parent company. However, challenges remain in optimizing digital engagement and responsiveness. This study contributes to understanding how digital marketing strategies influence consumer trust in the financial services sector, particularly in regional financing institutions.